PENINGKATAN KREATIVITAS MELALUI MEDIA KERTAS KOKORU PADA ANAK USIA DINI DI TK KARTIKA XIX-43 CIMAHI - Sri Wulandari; Arifah A Riyanto (IKIP Siliwangi, 2018)
This research stems from the concerns of researcher who see the less varied of the media used by the teacher when giving creativity learning to the students, in Kindergarten of Kartika XIX-43 Cimahi. This indicates not yet optimal learning by teachers in trying to increase creativity in students. Therefore, the aim of this researcher is to make changes by using kokoru paper media to improve the creativity of children of group B. and to describe the objective condition of learning in kindergarten of Kartika XIX-43 Cimahi, effort, and strategy, results achieved, and difficulties experienced by teachers on while learning creativity to improve children's creativity. As an educator of course must be much innovative and looking for a sharp strategy for learning creativity, because stimulates creativity early is very important to form a child more creative and independent to face his life that will come.